ПЕЩЕРЫ КАК ОБЪЕКТ ПАЛЕОНТОЛОГИЧЕСКИХ ИССЛЕДОВАНИЙ (К ИСТОРИИ ИЗУЧЕНИЯ. МУЗЕЙНЫЕ КОЛЛЕКЦИИ) - Стародубцева И.А.; Кузнецова Т.В.; Басова В.Б. (Издательско-полиграфический центр «Научная книга», 2016)
At the abstract the history ofpaleontological investigations o f caves in Russia is shortly presented. The main attention is focused on contribution ofl.D. Chersky. He is the founder o f the study caves that contain animal s bones. There is an analysis o f bone s material that resides at the Vernadsky State Geological Museum o f RAS. It is listed the mammal bone s materialfrom Smelovskay, Ignatievskaya, Serpievskaya, Kushlamatskaya and Murodymovskaya caves. These caves located at the South Ural and were excavated during 60-years o f XX century.
CAVES AS AN OBJECT OF PALEONTOLOGICAL INVESTIGATIONS
Keywords: Пещеры; палеонтология; музейные коллекции